Jagung Hibrida Genjah: Prospek Pengembangan Menghadapi Perubahan Iklim - Muhammad Azrai (Iptek Tanaman Pangan, 2013)
Global climate changes threaten the sustainability of maize production and maize consumption. Early maturing, high yielding hybrid maize varieties could be used as an adaptive measure to the climate changes. The national breeding program had released two hybrid varieties, Bima 7 and Bima 8, with yield potential of more than 10 t/ha and matures in 90 days after planting. The breeding research at ICERI is supported by the molecular techniques. Using the SSR markers showed that 24 combinations of drought tolerant inbred lines and 15 combinations of acid-tolerant inbred lines produced high level of heterosis (>75%). These inbred line combinations could be potentially developed into superior hybrids with early maturity. Three ICERI elite inbred lines of yellow grain color and tolerant to downy mildew had been top crossed by using 41 inbred lines of white grain color, super-early maturing, tolerant to drought and high temperature, obtained from CIMMYT-Kenya outreach program. This activity is part of the joint research between CIMMYT and some maize-producing countries in Asia to develop super early maturing hybrid maize, tolerant to drought. By utilizing molecular marker techniques as a tool for selection, it is expected that within the next 3-4 years, this research collaboration could result an early maturing maize tolerant to drought, high temperature and downy mildew disease. Thus, breeding research to develop early maturing hybrid maize could be the solution to anticipate the climate changes.